2005
DOI: 10.1161/01.cir.0000157144.24888.7e
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Progenitor Cells Are Rapidly Recruited to Myocardium and Mediate Protective Effect of Ischemic Preconditioning via “Imported” Nitric Oxide Synthase Activity

Abstract: Background-The function of bone marrow-derived endothelial progenitor cells (EPCs) in repair of ischemic tissue has been the subject of intense scrutiny, and the capacity of these cells to contribute significantly to new blood vessels remains controversial. The possibility that EPCs could act as reservoirs of cytokines has been implied by several observations; however, a specific role for cytokine delivery has not been identified. Methods and Results-We performed a series of experiments that revealed the rapid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
181
1
5

Year Published

2007
2007
2012
2012

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 233 publications
(195 citation statements)
references
References 51 publications
8
181
1
5
Order By: Relevance
“…Furthermore, animal studies have shown that transplanted BM cells or BM-derived EPCs contribute to the processes of neovascularization 41,44 and the development of collateral vessels that contribute to more rapid recovery of blood flow in the ischemic areas. 13,23,[41][42][43] Our BM transplantation data showing that transplantation of young WT but not p75KO BM MNCs into old p75KO mice rescued ischemic limbs from autoamputation suggest that ischemia-induced neovascularization and mobilization of EPCs from BM are mediated, at least in part, by TNFR2/p75 signaling.…”
Section: Goukassian Et Al Tnfr2/p75 and Neovascularization 759mentioning
confidence: 99%
“…Furthermore, animal studies have shown that transplanted BM cells or BM-derived EPCs contribute to the processes of neovascularization 41,44 and the development of collateral vessels that contribute to more rapid recovery of blood flow in the ischemic areas. 13,23,[41][42][43] Our BM transplantation data showing that transplantation of young WT but not p75KO BM MNCs into old p75KO mice rescued ischemic limbs from autoamputation suggest that ischemia-induced neovascularization and mobilization of EPCs from BM are mediated, at least in part, by TNFR2/p75 signaling.…”
Section: Goukassian Et Al Tnfr2/p75 and Neovascularization 759mentioning
confidence: 99%
“…MI was induced by ligating a left anterior descending (LAD) coronary artery as described previously. 19,20 Briefly, after the fourth to fifth intercostals space was opened, the heart was exteriorized, and the pericardium was incised. Thereafter, the heart was held with forceps, and MI was induced by ligating the LAD coronary artery at just the proximal site of the bifurcation of diagonal branch with a 7-0 (for mice)/6-0 (for rats) nylon suture.…”
Section: Surgical Proceduresmentioning
confidence: 99%
“…The tissues were embedded in OCT compound (Sakura FineTek, Japan) and sectioned at 1 mm for rats and 0.5 mm for mice just below the LAD ligation level at 5-mm thickness as described previously. 19 To measure fibrosis area, Masson's Trichrome staining was performed, and the fibrosis area (blue) was measured and calculated as the percent of the area of fibrosis to entire cross-sectional area of LV by using the NIH Image J 1.42 software and Adobe Photoshop CS4 (Adobe Systems, San Jose, CA, USA) software.…”
Section: Histological Analysismentioning
confidence: 99%
See 2 more Smart Citations